2007
DOI: 10.1007/s00436-007-0546-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of immunocompetence and parasitism in chub (Leuciscus cephalus), a freshwater cyprinid fish

Abstract: Seasonal variation of water characteristics, predominantly temperature, is considered to strongly affect fish physiology and immunology. In nature, this variation directly influences the life cycle especially in fish parasites, but the infection of parasites is also altered by the host immune response. This study is aimed to analyze the seasonal changes in selected physiological and immunological parameters, the latter a potential measure of fish immunocompetence. Moreover, the seasonal changes in metazoan par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…Indeed, the investigation of reproductive-immune interactions in fish has demonstrated that sexual maturation is often related to both innate and adaptive immune responses. These interactions affect innate immune proteins (Kumari et al 2006;Bowden et al 2007;Morgan et al 2008), acquired antibodies (Browser and Munson 1986;Steine et al 2001), and the number and proportion of leukocytes (Lamková et al 2007). Temperature and, to a lesser extent, other factors such as photoperiod appear to be the major cues driving these seasonal changes in immune markers (Bowden et al 2007).…”
Section: Interactions Between the Reproductive And Immune Systems In mentioning
confidence: 98%
“…Indeed, the investigation of reproductive-immune interactions in fish has demonstrated that sexual maturation is often related to both innate and adaptive immune responses. These interactions affect innate immune proteins (Kumari et al 2006;Bowden et al 2007;Morgan et al 2008), acquired antibodies (Browser and Munson 1986;Steine et al 2001), and the number and proportion of leukocytes (Lamková et al 2007). Temperature and, to a lesser extent, other factors such as photoperiod appear to be the major cues driving these seasonal changes in immune markers (Bowden et al 2007).…”
Section: Interactions Between the Reproductive And Immune Systems In mentioning
confidence: 98%
“…The interaction between parasitism, water contamination and condition factor is complex, being influenced by various biotic and abiotic factors (Escher et al 1999, Thomas et al 2000, Lamková et al 2007, Pervin and Mortuza 2008, Tavares-Dias et al 2008, Arafa et al 2009). None the less water quality (with particular reference to pollutants such as heavy metals) has been shown to negatively affect monogenean parasite numbers and distribution (Dušek et al 1998, Galli et al 2001, Marcogliese 2004, Blanar et al 2009).…”
Section: Water Quality Variablesmentioning
confidence: 99%
“…temperature, photoperiod, environmental pollution, etc. (Nikoskelainen et al, 2004;Magnadóttir, 2006;Lamkova et al, 2007;Morgan et al, 2008;Valenzuela et al, 2007;Tolarova et al, 2014) as well as biotic factors i.e. pathogens or parasites (Zapata et al, 1992;Bowden et al, 2007).…”
Section: Introductionmentioning
confidence: 99%